I. Kant on Lithuanian Language and Culture - Rickevičiūtė, Kristina (Problemos, 1968)
Historical documents and arguments advanced by some biographers of I. Kant show that, at least, three generations of the philosopher’s ancestors were inhabitants of Prussian Lithuania the population of which, at that time, consisted mainly of Lithuanians. Artisans themselves, I. Kant’s parents and, in his youth, the philosopher himself, must have had ample opportunity for intercourse with the oppressed common people. Therefore, it can be assumed that I. Kant knew the distinctive character of the Lithuanian of Prussia, the peculiarities of his mode of life and culture. To corroborate this assumption reference is made in the present paper to a certain document – a preface written by I. Kant to the Lithuanian-German and German-Lithuanian dictionary compiled by Ch. Mielcke and published in the year 1800. Guided by the general principle that one’s mother tongue is a perfect means to mould a person’s character and personality, I. Kant stands not only by the Prussian Lithuanian, who “is worthy of the preservation of the peculiarities of his character”, but also defends the rights of other nations under Prussian rule to practise a pure native language in schools and in church.